Synthesis and In Vitro Antimycobacterial and Antibacterial Activity of 8-OMe Ciprofloxacin-Hydrozone/Azole Hybrids - Xu, Zhi (Molecules, 2017)
A series of novel 8-OMe ciprofloxacin (CPFX)-hydrazone/azole hybrids were designed, synthesized, and evaluated for their in vitro biological activities. Our results reveal that all of the hydrozone-containing hybrids (except for 7) show potency against Mycobacterium tuberculosis (MTB) H(37)Rv (minimum inhibitory concentration (MIC): <0.5 μM), which is better than the parent drug CPFX, and comparable to moxifloxacin and isoniazid, some of the tested Gram-positive strains (MIC: 0.06–4 μg/mL), and most Gram-negative strains (MIC: ≤0.03–4 μg/mL).